Progress towards Schistosomiasis Elimination: Application of Sensitive Diagnostic Techniques - Amal Farahat Allam; Hoda Fahmy Farag; Mervat Mostafa Osman; Nancy Abd-elkader Hagras; Mohamed Abdel Rahman Ahmed; Adel Zaki; Rashad Abdul-Ghani; Amel Youssef Shehab (Longdom Publishing, 2018)
Objective: Pursuing successful control programs aiming at schistosomiasis elimination, the diagnostic performance of Kato-Katz, urine Circulating Cathodic Antigen (CCA) point of care rapid test and real-time PCR techniques were compared for the detection of Schistosoma mansoni among school children with different infection intensities. Methods: Stool and urine samples were collected from 110 school children after obtaining the consent of their parents and school guardians. The study was conducted in Motobus village, Kafr El-Sheikh governorate, Egypt. The collected stool samples were examined after Kato Katz (two slides, 41.7 mg each). Urine specimens were examined for S. haematobium by filtration technique and were tested for S. mansoni by POC-CCA. For of real time PCR, part of each stool sample was kept at -20C until used. Results: All the examined children were negative for S. haematobium. The performance of the three tests revealed that examination of double Kato-Katz smears detected S. mansoni infection in 51% of school children, where most of them had low infection intensity (64%). However, higher S. mansoni prevalence of 83% and 60% were diagnosed by real-time PCR and CCA, respectively. It was also found that real-time PCR detected a higher proportion of S. mansoni negative cases after Kato-Katz- compared to CCA (70% and 22%) respectively. Kato-Katz, CCA and real time PCR showed similar results with moderate and heavy infection intensities. Increasing the number of cycles of real time PCR to 40 cycles could detect the low infection intensity. Conclusion: To move towards schistosomaisis elimination, real time PCR due to its great sensitivity is suitable for established control programs to detect cases overlooked by Kato-Katz technique and CCA test. The adoption of this technique can enhance the monitoring of Schistosomiasis mansoni control measures in pre-elimination or elimination settings.